2020
DOI: 10.1029/2019jb018314
|View full text |Cite
|
Sign up to set email alerts
|

Fast Stokes Flow Simulations for Geophysical‐Geodynamic  Inverse Problems and Sensitivity Analyses Based On Reduced Order Modeling

Abstract: Markov chain Monte Carlo (MCMC) methods have become standard in Bayesian inference and multi‐observable inversions in almost every discipline of the Earth sciences. In the case of geodynamic and/or coupled geophysical‐geodynamic inverse problems, however, the computational cost associated with the solution of large‐scale 3‐D Stokes forward problems has rendered probabilistic formulations impractical. Here we present a novel and extremely efficient method to produce ultrafast solutions of the 3‐D Stokes problem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 66 publications
(160 reference statements)
0
24
0
Order By: Relevance
“…Previous work has shown that RB can speedup the numerical solutions of complex problems by several orders of magnitude without compromising the accuracy of the solutions (e.g. Ortega-Gelabert et al, 2020;Lieberman et al, 2010;Chen et al, 2010;Rozza et al, 2007Rozza et al, , 2013Florentin & Díez, 2012;Cui et al, 2015). In this paper, we will show that staggering gains in computational time can also be achieved for the 3D MT problem.…”
Section: Reduced Basismentioning
confidence: 73%
See 4 more Smart Citations
“…Previous work has shown that RB can speedup the numerical solutions of complex problems by several orders of magnitude without compromising the accuracy of the solutions (e.g. Ortega-Gelabert et al, 2020;Lieberman et al, 2010;Chen et al, 2010;Rozza et al, 2007Rozza et al, , 2013Florentin & Díez, 2012;Cui et al, 2015). In this paper, we will show that staggering gains in computational time can also be achieved for the 3D MT problem.…”
Section: Reduced Basismentioning
confidence: 73%
“…Another way of further achieving a small basis size is to seek for accurate solutions only within specific regions of the numerical domain (e.g. Ortega-Gelabert et al, 2020;Alvarez Aramberri, 2015). This stems from the fact that in many practical applications we are not interested in high accuracy at every point inside the numerical box, but rather within a restricted region.…”
Section: Efficiency Of the Rb+mcmc Methodsmentioning
confidence: 99%
See 3 more Smart Citations